Characteristics and Properties of Lemongrass (Cymbopogan Citratus): A Comprehensive Review - Zatil Hafila Kamaruddin; Ridhwan Jumaidin; Mohd Zulkefli Selamat; R.A. Ilyas (Journal of Natural Fibers, 2022)
Lemongrass (globally known as Cymbopogan citratus) belongs to the Poaceae family which is well known as a source of cellulose, hemicellulose, and lignin. This review addresses the structure, applications, and properties of lemongrass. This plant is extensively used in pharmacological activities due to its antiseptic, antibacterial, antifungal, and anti-inflammatory properties. Previous studies had primarily focused on using its constituent biological activities in food preservation, therapeutic applications, cosmetics, and agriculture. Therefore, this comprehensive review covers lemongrass as a source of cellulosic matter; for instance, as an adsorbent and as a raw material for producing biocomposite. Recently published work on emergent types of lemongrass fibers is also reviewed.